Probiotics in gastroenterology - Fric, P (Zeitschrift fur Gastroenterologie, 2002)
Probiotics are defined as live microorganisms of human origin. Their use may favorably influence human health and ameliorate or prevent certain diseases. Prebiotics are non-digestible foodstuffs (fiber, oligofructans - "colonic foods"), which enter the colon and are metabolized by the probiotics. Probiotics should fulfill the following criteria: Phenotypic and genotypic classification, no pathogenic properties, human origin, application in the living state, resistance to gastric acid and bile, ability to adhere to colonocytes, ability to colonize the gut, clinically proved favorable health-effect, and safety. Experimental and clinical studies supplied evidence of the possible use of probiotics in the following diseases: Traveler's diarrhea, antibiotic-associated diarrhea, relapsing Clostridium difficile colitis, infantile diarrhea, rotavirus enteritis, inflammatory bowel disease, irritable bowel syndrome, colon cancer, peritonitis, acute pancreatitis, and diarrhea associated with HIV infection. Probiotics displayed the following effects in these studies: Involvement in production of essential nutrients of the colonic mucosa, beneficial effect on intestinal immunity, recovery of the disturbed gut mucosal barrier and prevention of microbial translocation, elimination of toxins and eradication of microbial pathogens, production of steroids from cholesterol and reduction of its pool in circulation, participation in regulation of intestinal functions, reduced incidence of chemically induced colon tumors in rodents. Probiotics open new therapeutic modalities in a number of diseases and it may be expected that their importance will increase with growing knowledge and experience.
Keywords: průjem; Colonic Neoplasms; probiotika; Diarrhea; Probiotics; kolitida; Humans; výsledek terapie; lidé; nádory tračníku; gastrointestinální nemoci; Gastrointestinal Diseases; Colitis; Treatment Outcome